A comparison of the effects of remote coaching HIIT training and combined exercise training on the physical and mental health of university students - Wang, Yu; Jia, Ningxin; Zhou, Yanan; Fu, Linlin; Fan, Lixia; Li, Bin (Frontiers in Psychology, 2023)
Aims: To compare the effects of remote coaching HIIT training and combined exercise training on the physical and mental health of university students. Methods: Sixty university students were recruited from Shandong Normal University and randomly divided into a HIIT group (n=30) and a AR group (n=30), with the HIIT group using high-intensity interval training and the AR group using aerobic plus resistance training for 8 weeks. Mental health indicators, fitness indicators and body composition indicators were measured at the beginning and end of the intervention. Results: After 8 weeks, among the mental health indicators, the results of the SCL-90 scale test showed significant improvements in the HIIT group in terms of total SCL-90 score, somatization, obsessive-compulsive disorder, interpersonal sensitivity, depression, hostility, and psychoticism (P＜0.05); the AR group showed significant improvements in psychoticism (P＜0.05). There were no significant differences between the two groups. The results on the PSQI scale showed a significant difference in sleep efficiency with an inverse improvement in scores in the HIIT group; there was no significant improvement in each test item in the AR group. The results of the between-group covariance showed significant differences in sleep efficiency and hypnotic medication in the HIIT group (P＜0.05). Among the fitness indicators, the HIIT group showed significant improvements in maximum oxygen uptake, grip strength and flexibility (P<0.05); the AR group showed significant improvements in back strength and flexibility (P<0.05). The results of the between-group covariance showed significant improvements in maximum oxygen uptake in the HIIT group (P＜0.01). Regarding body composition indicators, there was a significant improvement in Body weight, BMI,Body fat percentage and Waist-to-hip ratio in both the HIIT and AR groups (P<0.01). There were no significant differences between the two groups. Conclusion: HIIT and combined exercise training based on remote coaching had some improvement on fitness level and body composition of college students, HIIT was more advantageous in improving aerobic endurance, and HIIT based on remote coaching may have better effect than combined exercise in mental health.